European instructional lectures : Volume 14, 2014, 15th EFORT Congress, London, United Kingdom - Bentley, George (European Instructional Lectures, 2014)
This fourteenth volume in the EUROPEAN INSTRUCTIONAL LECTURES series continues the format of educational chapters from across Orthopaedics and Traumatology contributed by distinguished Orthopaedic Educators in Europe.   It provides current material and major advances covering a range of topics including:   ·       General Orthopaedics, Basic Science and Technology ·       Musculo-skeletal Tumours ·       Infections ·       Paediatric Orthopaedics ·       Trauma ·       Spine ·       Upper Limb ·       Hip ·       Knee ·       Leg, Ankle and Foot   All the chapters are based on lectures presented at the 15th EFORT Congress in London, England. The lectures are an authoritative source of information illustrated by radiographs, MRI, CT and PET Scans, operative photographs, tables and line drawings as appropriate. They are an invaluable source of instruction for Surgeons and Trainees alike. This book was edited by Professor George Bentley, Chairman, Scientific Publications Committee of EFORT.